The Politics of Knowledge in Using GIS for Land Management in India - Puri, S.; Sundeep Sahay (Information Systems Research, 2004)
This paper focuses on understanding the knowledge politics that inhibit effective use of geographic information systems (GIS) for managing the land degradation problem in India. It is argued that the issues of power and politics of knowledge are ubiquitously embedded in representation of the problem domain and the technology itself. Addressing these issues is an inseparable part of the challenges to information systems design and implementation. Theoretical perspective is first developed around political considerations involved in the co-construction and use of knowledge domains relevant to the design of GIS applications to address land degradation. This theoretical framework is drawn upon to analyze the politics of representation, the politics of invisible work, and the politics of institutions observed in the case of a GIS implementation in rural India. The analysis also demonstrates how the insidious impacts of such politics may be somewhat mitigated by creating socio-material networks to cultivate communicative action that leads to better design and technology acceptance by the end users.

Counter Networks, Communication and Health Information Systems: A Case Study from Mozambique - Emilio Mosse; Sundeep Sahay (Information Systems Perspectives and Challenges in the Context of Globalization, 2003)

Institutional Structures and Participation: Comparative Case Studies from India - Satish K. Puri; Sundeep Sahay (Information Systems Perspectives and Challenges in the Context of Globalization, 2003)